A change point method for Phase II monitoring of generalized linear profiles. Issue 1 (2nd January 2017) - Shadman, Alireza; Zou, Changliang; Mahlooji, Hashem; Yeh, Arthur B.
ABSTRACT: In this article, we adopt the change point approach to monitor the generalized linear profiles in phase II Statistical process control (SPC). Generalized linear profiles include a large class of profiles defined in one framework. In contrast to the conventional change point approach, we adopt the Rao score test rather than the likelihood ratio test. Simulated results show that our approach has a good performance over any possible single step change in process parameters for two special cases of generalized linear profiles, namely Poisson and binomial profiles. Some diagnostic aids are also given and a real example is introduced to shed light on the merits of our approach in real applications.